Advertising and its Psychological Characteristics in Economy (Eurasian Journal of Learning and Academic Teaching, 2023)
The article contains information about the history of advertising, the advertising of goods in Greece and Ancient Rome through oral and written advertising, and even branding. Early forms of advertising existed even in ancient times before Christ. The first advertisement that has come down to us, which is now kept in the British Museum, is said to be a record of the sale of a slave written on papyrus in Egypt.